Cost-effectiveness analysis of using onasemnogene abeparvocec (AVXS-101) in spinal muscular atrophy type 1 patients. Issue 1 (1st January 2019) - Malone, Daniel C.; Dean, Rebecca; Arjunji, Ramesh; Jensen, Ivar; Cyr, Phil; Miller, Beckley; Maru, Benit; Sproule, Douglas M.; Feltner, Douglas E.; Dabbous, Omar
ABSTRACT: Background : Spinal muscular atrophy type 1 (SMA1) is a devastating genetic disease for which gene-replacement therapy may bring substantial survival and quality of life benefits. Objective : This study investigated the cost-effectiveness of onasemnogene abeparvovec (AVXS-101) gene-replacement therapy for SMA1. Study design : A Markov model was used to estimate the incremental cost-effectiveness ratio (ICER), expressed as cost/quality-adjusted life year (/QALY), of AVXS-101 versus nusinersen over a lifetime. Survival, healthcare costs and QALYs were estimated using natural history data for SMA patients who achieved motor milestones (sitting/walking). Health utility weights were obtained from the CHERISH trial. Setting : USA; commercial payer perspective Participants : SMA1 infants Interventions : AVXS-101 was compared to nusinersen. Main outcome measure : The primary outcome was the ICER. Results : Expected survival (undiscounted) over a lifetime predicted by the model was 37.20 life years for AVXS-101 and 9.68 for nusinersen (discounted QALYs, 15.65 and 5.29, respectively). Using a potential AVXS-101 price range (2.5-5.0M/treatment), the average lifetime cost/patient was 4.2–6.6M for AVXS-101 and 6.3M for nusinersen. The ICER range was (-203, 072) to 31, 379 per QALY gained for AVXS-101 versus nusinersen, indicating that AVXS-101 was cost-effective with prices of ≤5M. Conclusion : Single-dose AVXS-101 was cost-effective compared to chronic nusinersen for SMA1 patients.